Pengaruh Pola Makan Terhadap Kesehatan Mental Peran Nutrisi Pada Mahasiswa - Dela Ananda Putri; Ahmad Ainur Ridho; Oktaviana Rahmawati; Rahma Septiana; Liss Dyah Dewi A (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
This study aims to explore the relationship between diet and mental health in college students. By understanding the role of nutrition in mental well-being, we can identify dietary strategies that can improve mental health and improve quality of life. Using a quantitative approach with survey methods, data was collected from 200 students at University X. The research results show that there is a significant correlation between consuming nutritious food and lower levels of stress and anxiety. These findings indicate the importance of healthy eating patterns in maintaining mental health among students.